Trypanosomosis prevalence in natural field-based infection: insights into systematic review and meta-analysis of studies from 1980 to 2018 on The Gambian ruminants with special emphasis on cattle - Olaniyan, Olawale Festus; Kaya, Ibrahim; Secka, Arss (Tropical animal health and production, 2021)
Consistent quantification of trypanosomes, the parasite responsible for African animal trypanosomosis, is important for effective surveillance, control, and eradication strategies. Here, we used a rigorously predefined protocol to search and select eligible publications that utilized either microscopy, serology, or molecular methods to investigate prevalence of trypanosomosis based on the presence of any of three most common Trypanosoma spp. ( T. congolense , T. vivax , and T. brucei ) in the field-based naturally grazed Gambian cattle, sheep, and goats. To combine results of studies on cattle through meta-analysis, sensitivity and subgroup analyses were carried out with the random effects model, and prevalence estimates of each study with 95% confidence intervals (CI) were presented with a forest plot. All the eligible studies utilized the buffy coat technique (BCT) to detect trypanosomes in the blood samples, while the more sensitive serological and molecular detection methods are yet to be widely exploited. Heterogeneity among the studies on cattle was moderate ( I 2 = 55%), and the pooled trypanosomosis prevalence based on the BCT was 5.2% (95% CI: 4.0–6.4). Meanwhile, estimated prevalence varied according to the trypanosome detection methods, study locations, types of publication, year, and length of observations. We could not pool the trypanosomosis prevalence in sheep and goats through meta-analysis due to small number of studies. The prevalence estimates based on the BCT ranged from 3.2 to 8.1% in goats and 2.8 to 10.6% in sheep. Even though there seems to be a slight decrease in trypanosomosis prevalence in cattle in one of the Gambian districts, there was no consistent trend across the years. It is thought that the literature search and formatting procedures presented in this study contribute to doing systematic reviews on the investigated subject and can be adapted for similar cases.